INOVASI PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Winda, Nurhaswinda; Afiska, Zely; Sarah, Nur; Nugraheni, Nonik; Jannah, Purwalis Miftahul; Novasari, Novasari; Rimarsha, Nasna; Putri, Nabila; Putri, Nurpita; Ramadhani, Novi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
Critical thinking is a fundamental skill essential for facing the challenges of the 21st century, and should therefore be taught from an early age. This study aims to assess the effectiveness of project-based learning (PjBL) in improving critical thinking skills in elementary school students. The study was conducted in the form of a two-stage classroom action (CAR) project involving fifth-grade students. The results showed a significant increase in students' critical thinking skills, as evidenced by their ability to analyze, evaluate arguments, and solve problems. The implementation of PjBL has been shown to encourage independent learning and increase student active engagement during the learning process. Keywords: Project-Based Learning, Critical Thinking Skills, Educational Innovation, Elementary School Students